Regulasi Emosi dalam Konteks Stres Akademik Remaja: Sebuah Pendekatan Edukatif - Evi Supriatun; Nafisah Itsna Hasni; Marsono Marsono (Journal of Telenursing (JOTING), 2026)
This study aims to examine the effect of an emotional regulation educational approach on academic stress levels in adolescents in Islamic boarding schools. The method used was a quantitative pre-experimental study with a one-group pretest–posttest design. The results showed a statistically significant decrease in mean academic stress scores after emotional regulation education (p < 0.05). In conclusion, an emotional regulation educational approach can be used as a promotive and preventive strategy to reduce academic stress in adolescents in Islamic boarding schools.   Keywords: Education, Emotional Regulation, Adolescents, Academic Stress